The Effect of Service Quality, Price, and Location on Purchasing Decisions in the Perspective of Islamic Economics at Sang Surya Mart, Perintis Kemerdekaan, Makassar City - Muh Nur R; A. Nur Achsanuddin UA; Moh Aris Pasigai (Jurnal Ilmiah Ekonomi Islam, 2023)
Trade competition in this globalization era is getting tighter, especially in marketing products and services. Various steps have been taken by entrepreneurs to increase purchases, such as paying attention to the factors of service quality, affordable prices, and strategic locations. The purpose of this study was to see the effect of service quality, price, and location on purchasing decisions at Sang Surya Mart. The research method used is a quantitative method. Primary data analysis through a questionnaire with 100 respondents. The questionnaire scale is a Likert scale 1-5. Multiple linear regression was applied as an analytical method which was processed using SPSS 26.0 and classical assumption tests and hypothesis tests were carried out. The research findings found that service quality partially influences purchasing decisions. Meanwhile, price and location partially have no effect on purchasing decisions. The variables of service quality, price, and location show a significant relationship to the purchase decision simultaneously.